A multiscale DEM-FEM approach to investigate the tire–pavement friction. Issue Volume 19:Issued 5(2018) (4th May 2018) - Hou, Yue; Wang, Xinfei; Sun, Wenjuan; Wang, Linbing
Abstract: Fundamental understandings of the pavement-tire friction are vital to improve the design of asphalt pavements. Most of the current research on pavement-tire friction is based on Finite Element Method (FEM), which is relatively complex and difficult to simulate the discontinuity during friction. To overcome the limitations, in this paper, the pavement–tire friction process is investigated using a coupled Multi-scale Discrete Element Method (DEM) – FEM approach. The benefit of such a multiscale method is that DEM has the advantage of simulating the discontinuity behaviour during friction, and FEM is good at simulating the continuum material with low computation consumption. The multi-scale approach provides an innovative and promising approach to simulate the tire-pavement friction behaviour.